The Role of Toko Tani Indonesia (TTI) to Supply Chain and The Establishment of Rice Prices in Sragen District - Putri, Hilda Anugrah; Irianto, Heru; Antriyandarti, Ernoiz (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
This research examines the role of Toko Tani Indonesia (TTI) in the rice supply chain and price determination in Sragen Regency, Central Java, Indonesia. Using a descriptive analysis approach, the study focused on Sragen, a major rice production center. The samples for this investigation were selected purposively from datasets provided by eleven Community Food Business Institutions and Indonesian Farmer’s Stores that have been recorded in the Office of Agriculture and Food Security of Sragen Regency. The Food Supply Chain Networking (FSCN) model and rice price formation were analyzed qualitatively, while supply chain performance and value-added (VA) were assessed quantitatively. Results revealed a significant reduction in the rice supply chain stages from 6–7 to just 3, improving efficiency. Margins for partner farmers and TTI were calculated at IDR 1,600 per kilogram (51.13% of total margin share) and IDR 300 per kilogram, respectively. Inventory turnover was 12 times annually, with inventory days of supply for farmer groups at 30 days and a cash-to-cash cycle of 37 days. VA analysis showed farmers contributed 72% of total value (IDR 376,216,168), LUPM 26% (IDR 136,678,955), and TTI 2% (IDR 8,090,000). TTI supports farmers by purchasing grains at fair prices, ensuring effective marketing, maintaining rice availability, and stabilizing prices, thus playing a critical role in the community's food security efforts.